Socio-Economic Analysis of Rice Farmers in the New Normal Era in Tabir Lintas Sub-District Merangin District - Evo Afrianto; Aprilia Susanti; Pitriani Pitriani; Lili Suryani (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2024)
The COVID-19 pandemic has significantly impacted the agricultural sector, especially for small-scale farmers in rural areas who face challenges in maintaining the sustainability of their farming businesses. Koto Baru Village, Tabir Lintas Sub-district, Merangin District, is the only village actively growing paddy rice during the pandemic. This condition is interesting to study in farmers' social and economic contexts during the transition era to the New Normal. This study aims to analyze the socio-economic conditions of wet-rice farmers and assess the feasibility of farming in the New Normal era of the COVID-19 pandemic. This research was conducted using the survey method from January 30 to March 1, 2021. The research sample was 54 farmers selected from 105 farmer group members by proportional random sampling. The variables studied included the level of education, income, number of family dependents, health, overall socio-economic aspects of farmers, and aspects of farm business feasibility. Primary data were collected through interviews with structured questionnaires, while secondary data were obtained from relevant agencies and supporting literature. Data analysis was done descriptively using a Likert scale to describe farmers' socio-economic conditions. The feasibility of farming was analyzed through a financial approach, including the calculation of total costs, revenue, income, and R/C ratio analysis. The results showed that most farmers were in the low socio-economic category, with limited education, low income, and high family dependency. Nevertheless, wetland rice farming still shows promising economic value based on the results of financial calculations.